The Relationship between Physical Activity, Body Mass Index and Body Composition among Students at a Pre-University Centre in Malaysia - HW, You; PL, Tan; AF, Mat Ludin (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: Physical activity is an essential element in our daily life that leads to long-term health benefits. Physical activity refers to movement of the body that requires energy. Body mass index (BMI) indicates a ratio of body weight to squared height, which is a useful health indicator. On the contrary, body composition describes the body by measuring percentages of fat and muscle in human bodies. MATERIALS AND METHODS: This cross-sectional study aimed to determine the relationship between physical activities, BMI and body composition among pre-university students from one of the universities in Selangor, Malaysia. Stratified random sampling was employed to recruit 70 pre-university students into this study. RESULTS: From the study, 50% of the respondents are categorized as minimally active. In addition, there is significant difference between the physical activity levels of male and female respondents. The relationship between physical activity and BMI indicates a very weak negative correlation. Similarly, the correlation between physical activity and fat mass is a weak negative relationship. Meanwhile, there is a weak positive correlation between physical activity and muscle mass. CONCLUSION: Therefore, it can be concluded that when physical activity increases, BMI and body fat mass will decrease, while muscle mass will increase. Moreover, it was shown that there was a significant relationship between physical activity and body composition.